An Approach to Give First Rank for Website and Webpage Through SEO - Shrivastva, Rajneesh; Mewada, Shivlal; Sharma, Pradeep (International Journal of Computer Sciences and Engineering, 2014)
Now a day’s internet is one of the best ways to access any information. If a person make fully optimized site then definitely they can achieve top first position of their site in Google page result. As you know Google provide top 10 result so if your site is not visible in top first page then whatever information you want to give for people it’s not obtain properly . This paper represents how any person that wants to make their own website can promote a site with the help of my SEO Methodology. This paper is fully based on keyword research it means if a person is able to optimize right keyword whatever keyword used currently then its sure that their site will be on top first page on Google page result. Today every person has their own website so it is very difficult to place the site in first position on Google page result. This paper will solve this problem.